Finding the future in policy discourse: an analysis of city resilience plans. Issue 5 (4th May 2021) - Taylor, Zack; Fitzgibbons, Joanne; Mitchell, Carrie L.
ABSTRACT: Managing future uncertainty is the essence of planning. How planners conceptualize the future therefore has important practical and normative implications as contemporary decisions have long-term impacts that may be irreversible and distribute costs and benefits across society. A discourse analysis of strategies prepared under the 100 Resilient Cities programme reveals that while they are ostensibly forward-looking and cognizant of uncertainty, most presume a knowable future (epistemic certainty) and focus on well-understood or recently experienced risks. Few acknowledge the future's inherent unknowability (ontic uncertainty). Those that do emphasize community self-help; others describe top-down, government-led initiatives. Most strategies also present an image of societal consensus, downplaying the potential for legitimate disagreement over means and ends (discursive uncertainty). These findings suggest that new conceptualizations of future uncertainty have had limited impacts on planning practice.